Investigating the stability of superoxide ion generated in ionic liquids and the conversion of sulfur compounds / Muna Hassan Ahmed Ibrahim - Muna, Hassan Ahmed Ibrahim (2016)
Superoxide ion (O2•−) is a reactive oxygen species which plays a primary role in numerous applications. This radical anion has not received much interest for industrial use due to it reactivity with most solvents. In the last decade, O2•− was found to be stable in ionic liquids (ILs), which have many benefits over conventional aprotic solvents. Nevertheless, the stability of O2•− with ILs has not been well studied in the long term which is essential for industrial applications. In the present work, O2•− stability and kinetics were examined with various ILs based on morpholinium, ammonium, imidazolium, piperidinium, pyrrolidinium and sulfonium cations, paired with anions such as bis(trifluoromethylsulfonyl)imide[TFSI], octylsulfate, tetracyanoborate and tris(pentafluoroethyl)trifluorophosphate. Stable ILs were used as media for the reaction of O2•− with sulfur compounds. The physical properties of somes stable ILs were determined as another key factor for their industrial use as media for O2•− generation. Cyclic voltammetry (CV) was used to electrochemically generate O2•− and to investigate the ion’s short term stability in ILs; the observations were successful generation of O2•− and short term stability of O2•− in the ILs. However, the small oxidation peak obtained for triethylsulfoniumbis(trifluoromethylsulfonyl)imide at 9 mV/s suggested O2•− might be unstable in this IL. The electrochemical generation of O2•− in the studied ILs was a quasi-reversible process. Subsquently, ultraviolet-visible spectrophotometry was employed to investigate the long term stability of O2•− and to study the kinetics of O2•− reactions. The rate constant of the reaction of O2•− generated in dimethyl sulfoxide containing ILs was calculated based on pseudo 1st order (k1) and pseudo 2nd order (k2). The value of k1 ranged from 7.049 ×10−6 to 2.645×10−3 s−1 while k2 ranged from 4.732×10−3 to 3.547 M−1 s−1. The generated O2•− stability was found to be dominated by the type of cation in the order morpholinium>ammonium>piperidinium≈pyrrolidinium>>imidazolium>>sulfonium. The O2•− was unstable in triethylsulfoniumbis(trifluoromethylsulfonyl)imide, 1-butyl-3- methyl-imidazoliumoctylsulfate and 1-butyl-3-methylimidazoliumhexafluorophosphate. Chemically generated O2•− in 1-butyl-1- methylpyrrolidiniumbis(trifluoromethylsulfonyl)imide, N-methoxyethyl-Nmethylmorpholiniumbis( trifluoromethylsulfonyl)imide, 1-(2-methoxyethyl)-1- methylpiperidiniumtris(pentafluoroethyl)trifluorophosphate, 4-(2-methoxyethyl)-4- methylmorpholiniumtris(pentafluoroethyl)trifluorophosphate and ethyl-dimethylpropylammoniumbis( trifluoromethylsulfonyl)imide was utilized for the conversion of two types of sulfur compounds, thiophene (TH) and 2-methylthiophene (2-MTH). The conversion percentage and formation of by-products were analyzed using both HPLC and GC/MS. The conversion percentage ranged from 35 to 99% for TH and from 20 to 96% for 2-MTH. A mechanism was proposed for this conversion. The products of the conversion were identified as H2O, CO2, and SO3. Furthermore, the effect of temperature on this reaction was studied. The ILs did not only behave as media for the generation of O2•− but also possessed catalytic activity to accelerate the reaction rate between O2•− and substrates. The physical properties, namely density, viscosity, conductivity and surface tension of five stable ILs containing [TFSI] anion paired with 1-(2-methoxyethyl-1- methylpiperidinium, 1-(2-methoxyethyl)-1-methylpyrrolidinium, N-methoxyethyl-Nmethylmorpholinium, N-ethyl-N,N-dimethyl-2-methoxyethylammonium and ethyldimethyl- propylammonium respectively were determined between 25 to 80 °C. The ILs followed Arrhenius behavior for conductivity and viscosity while a linear trend was observed for surface tension and density.